On multi-phase machines and current harmonic injection for torque capability improvement - De Gaetano, Daniele (2022)
The increased energy demand and the need for electrical machines capable to deliver high torque and power in small volumes is pushing the research community to identify suitable solutions for this target. Nowadays, electrical machines are deeply used also in applications where the weight containment is important such as automotive and aerospace.